2016
DOI: 10.1136/bmjopen-2016-012356
|View full text |Cite
|
Sign up to set email alerts
|

ImmunoglobuliNin theTreatment ofEncephalitis (IgNiTE): protocol for a multicentre randomised controlled trial

Abstract: IntroductionInfectious and immune-mediated encephalitides are important but under-recognised causes of morbidity and mortality in childhood, with a 7% death rate and up to 50% morbidity after prolonged follow-up. There is a theoretical basis for ameliorating the immune response with intravenous immunoglobulin (IVIG), which is supported by empirical evidence of a beneficial response following its use in the treatment of viral and autoimmune encephalitis. In immune-mediated encephalitis, IVIG is often used after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…We also explored the effects of IVIG treatment alone and in combination with ACV in HSV-infected and uninfected mice, because IVIG has been used to treat HSV encephalitis (HSE) and is also a frontline therapy for autoimmune encephalitis, which is triggered by HSE and other insults [ 58 60 ]. Moreover, IVIG is being evaluated in a randomized control trial for children with all-cause encephalitis to determine whether neurological outcomes are improved, compared to standard antiviral therapy alone, which is similar to our behavioral study that generated paradoxical results [ 15 , 61 ]. Reports that IVIG’s antigenic repertoire includes reactivities to a variety of gut commensal antigens and metabolites have increased recently [ 62 64 ], which is consistent with a report that gut commensals can somehow trigger systemic IgG responses under homeostatic conditions that protect against systemic infection [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 77%
“…We also explored the effects of IVIG treatment alone and in combination with ACV in HSV-infected and uninfected mice, because IVIG has been used to treat HSV encephalitis (HSE) and is also a frontline therapy for autoimmune encephalitis, which is triggered by HSE and other insults [ 58 60 ]. Moreover, IVIG is being evaluated in a randomized control trial for children with all-cause encephalitis to determine whether neurological outcomes are improved, compared to standard antiviral therapy alone, which is similar to our behavioral study that generated paradoxical results [ 15 , 61 ]. Reports that IVIG’s antigenic repertoire includes reactivities to a variety of gut commensal antigens and metabolites have increased recently [ 62 64 ], which is consistent with a report that gut commensals can somehow trigger systemic IgG responses under homeostatic conditions that protect against systemic infection [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 77%
“…Although IVIg has been used off-label for the treatment of encephalitis caused by enterovirus 71, Japanese encephalitis virus, and West Nile virus, there is a lack of clinical studies on the efficacy and safe-ty of IVIg for viral encephalitis [25][26][27]. Since 2015, the first randomized controlled trial, has been conducted to evaluate the effect of IVIg treatment in pediatric encephalitis of any cause [28]. This clinical trial included 308 children (6 months to 16 years) across 30 hospitals in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…A small randomized trial has shown superiority of intravenous immunoglobulins (IVIG) to placebo in reducing seizure frequency in anti-leucine-rich, glioma-inactivated 1-antibody (anti-LGI1-Ab) and anti-contactin-associated protein-like 2antibody (anti-CASPR2-Ab) seropositive adult patients (7). Other randomized trials evaluating the efficacy of IVIG, rituximab and bortezomib are ongoing (8)(9)(10). We have set up a multicenter prospective observational study for a structured assessment of diagnostics and treatments applied in clinical routine in adult patients with autoimmune encephalitis.…”
Section: Introductionmentioning
confidence: 99%